Association of double product and pulse pressure with cardiovascular and all‐cause mortality in the LURIC study. Issue 12 (9th October 2020) - Yazdani, Babak; Kleber, Marcus E.; Yücel, Gökhan; Delgado, Graciela E.; Benck, Urs; Krüger, Bernd; März, Winfried; Krämer, Bernhard K.
Abstract: Systolic (SBP) and diastolic blood pressure (DBP) and mean arterial pressure (MAP) are risk factors for cardiovascular mortality (CVM). Pulse pressure (PP) is considered as an easily available marker of vascular stiffness and the double product (DP) as a marker of cardiac workload. Therefore, we have examined the predictive value of PP and DP in the Ludwigshafen Risk and Cardiovascular Health study, a monocentric cohort study of 3316 patients referred to coronary angiography. An increase of SBP or PP by 1mmHg increased the risk of CVM with hazard ratios of 1.009 (95% CI, 1.005‐1.012) and 1.016 (1.012‐1.020), respectively. Increasing DP by 100 mm Hg/min was associated with a 1.010 (1.007‐1.013) higher risk of CVM. In patient subgroups with coronary artery disease (CAD) and heart failure (HF), PP and DP predicted CVM better than SBP or MAP. In a multivariate analysis adjusted for sex, BMI, diabetes, eGFR, hazard ratios for CVM for z‐standardized PP, DP, SBP, and HR were 1.20, 1.16, 1.12, and 1.14. After adding age to the multivariate analysis, only DP and HR remained significant. We provide evidence that PP and DP are powerful predictors of CVM and all‐cause mortality in a CV medium‐ to high‐risk population, especially in patients with CAD and HF. While DP proved to be an independent predictor of cardiovascular and all‐cause mortality also in multivariate analysis, PP was no independent predictor in our cohort with widespread antihypertensive treatment (>85%). PP is associated with age, presence of diabetes, obesity, and impaired renal function.